FAKTOR YANG MEMPENGARUHI PENDAPATAN PADI ORGANIK DI PRINGSEWU, LAMPUNG - Wendy Prastyo; Zulkarnain Zulkarnain; Arif Ferdiansyah (Jurnal WACANA PERTANIAN, 2022)
A healthy lifestyle is a growing trend in society, the embodiment of a healthy lifestyle is through eating and drinking with organic products so that it becomes an opportunity for organic farmers. The research objectives: (1) to determine the income of organic rice farming, and (2) to determine the factors that affect the income of organic rice farming. The research was conducted in Pajaresuk Village, Pringsewu District, Pringsewu Regency in January 2022 with 30 organic rice farmers as respondents. The analytical method used is income analysis and multiple linear regression analysis. The results of the study: (1) organic rice farming income in Pajaresuk Village, Pringsewu District, Pringsewu Regency of Rp. 3,810,040 per 0.33 ha with an R/C Ratio of 2.01, and (2) land area (X1), business experience (X2), education level (X3), age (X4), and commodity prices (X7) significantly affect organic rice income.